Analisis Risiko Proyek Konstruksi Jalan Tol Menggunakan Metode Risk Matrix dan Relative Importance Index (RII) - Arief Budi Hartono; Mardiaman Mardiaman (Jurnal Talenta Sipil, 2026)
Toll road construction projects are characterized by high complexity and uncertainty due to the involvement of multiple stakeholders, regulatory constraints, and dynamic site conditions, which often lead to delays and cost overruns. Despite extensive studies on construction risk, existing approaches tend to apply fragmented methods that fail to simultaneously capture risk magnitude and prioritization in an integrated manner. This study aims to develop a comprehensive risk evaluation framework by integrating the Risk Matrix and Relative Importance Index (RII) to identify, assess, and prioritize risks in toll road construction projects. A quantitative approach was employed using primary data collected through structured questionnaires distributed via Google Form to project stakeholders between January and February 2026. The identified risk variables were analyzed by calculating risk scores based on probability and impact, followed by RII to determine risk prioritization. The results were further visualized using a risk heatmap to enhance interpretability. The findings reveal that the most critical risks are predominantly associated with non-technical factors, particularly land acquisition delays, land readiness issues, and inter-agency coordination. These risks consistently rank highest in both risk matrix and RII analyses, indicating strong agreement between risk severity and stakeholder perception. Additionally, operational risks such as construction delays and traffic disruptions also contribute significantly to project performance degradation. This study contributes by proposing an integrated and visually enhanced risk assessment framework that bridges the gap between quantitative evaluation and practical decision-making. The proposed approach provides a more comprehensive understanding of risk distribution and prioritization, offering practical implications for improving risk management strategies in large-scale infrastructure projects, particularly in developing countries.